Aging in place and elderly mobility habits: Evidence from Italian national surveys - Rossi, Federica (European Spatial Research and Policy, 2024)
The aim of the paper is to provide an empirical framework of the ageing process in Italy, with a focus on aging in place and mobility behaviour of the elderly, as emerging from two national surveys: the “Aspects of Daily Life” survey by ISTAT and the ISFORT mobility survey. Results show that the Italian cities and towns are sufficiently age-friendly, with some improvement opportunities to be implemented. Loneliness and isolation represent a warning sign, hindering the aging in place. Finally, the study confirms that the Italian older adults use public transport only a few times, in favour of private cars.